al-Masa’il al-Nahwiyyah (Dirasah Taqabuliyyah Baina Madrasah al-Bashrah wa al-Kufah) - Roviin (ALSINATUNA, 2018)
When Islam spread to some Arabian peninsula, Arabs were also scattered to various regions, they communicated with non-Arabs and assimilated with each other. As a result, a new generation emerged that could not preserve the authenticity of its language. Therefore, the Arabs became distorted from the authenticity of their language. The emergence of many Arabic aberrations led to the need to preserve the originality of the Arabic language. This article attempts to analyze the problem of Arabic deviation. Abu al-Aswad al-Duwali was the first who establish Arabic grammars on the orders of Caliph Ali ibn Abi Talib. After Abu al-Aswad al-Duwali, emerging famous grammars were divided into Madrasa of Bashra and Madrasa of Kufa, each of these Madrasas had characteristics and differences. The difference between these two Madrasas is enormous and in many issues. The distinguishing difference between these two Madrasas is that the Madrasa of Bashra is more stringent in terms of Arabic grammars, while Madrasa of Kufa is more loose in it.